Knowledge generation in the wake of the Fukushima Daiichi nuclear power plant disaster - Kaur, Kiran; Ng, Kwan Hoong; Kemp, Ray; Ong, Yin Yee; Ramly, Zaharah; Koh, Ai Peng (Springer Verlag, 2019)
A disaster is a crisis situation that causes significant harm to humans, the environment, the economy, and impacts upon society’s ability to cope both during the event and with the aftermath. A disaster may escalate rapidly to reach unpredicted consequences. They can be naturally occurring, or man-made, or a combination of the two. In this study we have focused on the Fukushima Daiichi nuclear power plant accident of 2011 that subsequently unleashed a floodgate of scientific activities, including basic and applied research, technology development, policy reform, inter-disciplinary collaboration, citizen science and re-strategization of research networks. In this context, a bibliometric study has been conducted on 5455 publications on the Fukushima disaster indexed by Scopus for the 2011–2017 period. The aim is to identify key papers in the field, the most substantive contributors to the literature, and to begin to map out the emergence of a body of knowledge resulting from the disaster. The findings present main national and international collaborators on Fukushima disaster related research, as well as an indication of the major research themes evolving over the immediate years following the event. This allows for a deeper understanding of the longitudinal impact of a disaster on society and upon the international research community and its deliberations. © 2019, Akadémiai Kiadó, Budapest, Hungary.